The Role of the Tanah Datar Regency Nakerin Service in Empowering the Community of Nagari Situmbuk, Salimpaung District through the Development of the Traditional Embroidery Industry: Peran Dinas Nakerin Kabupaten Tanah Datar dalam Pemberdayaan Masyarakat Nagari Situmbuk Kecamatan Salimpaung melalui Pengembangan Industri Sulam Tradisional - Niken Ayu; Fitri Eriyanti (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research is motivated by the potential of the people of Nagari Situmbuk, Salimpaung District in the Kapalo Samek embroidery industry. Apart from maintaining cultural heritage in terms of embroidery, embroidery is also used as a source of livelihood for the community. The department that has a role in helping the development of the embroidery industry in Tanah Datar Regency is the Department of Manpower and Industry. Some of the problems that arise in empowering the community through the embroidery industry are lack of craftsman skills, lack of craftsman innovation, many craftsmen who are inconsistent and networking. This research aims to analyze the role of the Tanah Datar Regency Nakerin Service in empowering the Nagari Situmbuk community in the traditional embroidery industry. This type of research is qualitative with descriptive methods. Data collection was carried out through observation and interviews. The results show that the Nakerin Service has carried out its role quite well, but not optimally. This can be seen from the lack of optimal training efforts provided by the department, the lack of information regarding the training being held and the lack of optimal digital marketing efforts by the department